Studying and fixing buggy code using ChatGPT - Ling, Yin (Nanyang Technological University, 2024)
As software projects become more and more complex, bugs are inevitably introduced. Bugs may lead to undesirable consequences such as software reliability issues or vulnerabilities in the code. Which may then lead to other undesirable financial issues. Hence, bug fixing tasks are important in the software development cycle as this is an important step in identifying defects or undesirable behaviour in the software. However, bug fixing is a difficult task, typically due to the complexity of software that is built over time. Hence, many automated methods have been experimented with to improve the efficiency of bug fixing tasks.